2022
DOI: 10.37546/jaltsig.pie10.1-4
|View full text |Cite
|
Sign up to set email alerts
|

Genki: A Case Study of Benefits for Foreigners Producing Theatre in a Japanese Regional Dialect

Abstract: This paper describes the Genki Tosaben Musical (Genki), a unique community theatre project in Kochi prefecture in Japan. Since 1996, foreigners living in Kochi have been creating original musical theatre productions in Tosaben, the local Japanese dialect, and touring the prefecture to raise money for charity and promote cross-cultural exchange. In this study, qualitative survey responses from 35 former participants in Genki were analyzed. Based on these survey responses, this paper explores the motivations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
2
1
0
Order By: Relevance
“…This study examined how performing live theatre in a foreign language outside a classroom setting influenced language learning and community integration among JETs in Kochi. The results of this study mirror previous results (Head, 2022) that found participating in Genki led to perceived increases in both language learning and community integration. Interviewees in this study pointed to improvements in spoken fluency due to practicing dialogue with native Tosaben speakers, as well as increased vocabulary knowledge through learning their lines.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This study examined how performing live theatre in a foreign language outside a classroom setting influenced language learning and community integration among JETs in Kochi. The results of this study mirror previous results (Head, 2022) that found participating in Genki led to perceived increases in both language learning and community integration. Interviewees in this study pointed to improvements in spoken fluency due to practicing dialogue with native Tosaben speakers, as well as increased vocabulary knowledge through learning their lines.…”
Section: Discussionsupporting
confidence: 88%
“…Meanwhile, both KM (fluent speaker) and EB (rudimentary speaking) saw creating a play in Japanese as more of a personal challenge than solely a language-learning opportunity. These motivations echo results from Head (2022), which showed that most participants in Genki had an existing love of performance and that the most common motivation for participating was the formation of social connections, with language learning being a secondary goal (although language learning did occur, as shown in the next section). Reasons for Joining Genki…”
Section: Participant Backgroundssupporting
confidence: 59%
See 1 more Smart Citation